HUBUNGAN SIKAP BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN DASAR PERANCANGAN TEKNIK MESIN SISWA KELAS X TEKNIK PEMESINAN DI SMK NEGERI 5 PADANG - Alfisutri Khaira; Nelvi Erizon; Ambiyar Ambiyar (Jurnal Vokasi Mekanika (VoMek), 2024)
Beside interaction, attitude is another factor that cause the lack of understanding in learning process. Learning attitude is needed for success and smoothness of the learning processed. The purposed of the studied was to determines the correlation between attitudes and learning outcomes and how much influence the two variables had. Quantitative research with correlation analysis is applied to find out the relationships between two variable. Result from data analysis using a hypothesis test with products moment correlations analysis obtaineds a correlations coefficient values of 0.454 with a sig value of 0.0009. From the result concludes thats theres is a relationship betweens the two variables, this happens because the value of sig < 0.005 is strengthened by the calculated r value of 0.361 and the r table value of 0.2706 meaning Ha is accept and Ho is reject whiled the value of the magnitudde of the influences betweens the two variables is 13, 06%, which means that attitude is one of the determine factor in the student learnings outcomes in this studied. The conclusions is thats there’s a positived correlation between attitudes and learn outcome of student of class X Mechanical Engineering at SMK N 5 Padang and from the result it’s known thats one of the factor in improving learning outcomes is attitude in learning. Learning outcomes can increase with a good learning attitude and vice versa.